Pedagogia da alternância: emancipação e territorialização nas Escolas Famílias Agrícolas - Costa, Agnaldo Chagas (2016)
This academic research aims to evaluate the assumptions from pedagogy of alternation adopted by Brazilian EFA (Agricultural Family Schools) network regarding its commitment to offer whole formation and environment development. Those expressions are interpreted in this academic research, respectively, as emancipatory education and territoriality action. They counted on 143 school units in end of the 2014 in Brazil. Original from French and result of the initiative of small farmers properties, this school model presents itself as a contextualized solution and alternative to help to solve education failure in the countryside. The hypothesis put forward is that the school would meet its assumptions for whole formation and development. The research was carried out in mind by Theodor Adorno critical theory and the geographic interpretation of Milton Santos. The research information were composed by interviews with pedagogical, administrative and political leaders from schools network, articles published in a specialized countryside education magazine and documentation gathered in the school unit from Orizona city in Goiás state. Furthermore this academic research proposes to bring out the pedagogy of alternation history, the family school model and to argue about understanding of urbanity/countrified and city/countryside culture concepts. As a result of research, it was found that the family school model meets very strongly in the environment development assumption, acting on territoriality and farmer settlement through its educational activities while pedagogical actions to take in the premise of whole formation collaborates very little to the education for emancipation and autonomy who turns out to be coerced by integrative strength of the school by itself. In additional, this study aimed, without proposing any hypothesis, check the evolution of the human development indicator and the countryside population from areas where the school units are localized in order to compare them with their own macro areas: federal state, region and country. As a result it obtained important statistical information to be taken into account at formulation of theoretical studies now investigated